Analisis Rasio Keuangan dan Price to Book Value terhadap Harga Saham Dengan Earning Per Share Sebagai Variabel Moderasi pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Clarysa Galuh Fitri; Ira Wikartika (Universitas Batanghari Jambi, 2022)
One of the consequences of the spread of the Covid-19 virus that has spread in the country is the losses experienced by several industries, the Food and Beverage industry being the industry most affected. Business actors are required to be more innovative in the midst of the current wave. Changes in behavior in society lead to changes in shares in the company. The existence of fluctuations in stock prices is certainly a consideration for investors who make investments. The purpose of the study was to analyze the effect of Profitability and Price to Book Value on stock prices by adding Earning Per Share as a moderating variable. The sample selection technique used purposive sampling and obtained 52 samples of companies. The research analysis method is Moderation Regression Analysis with the help of SPSS. With the results of research ROA and PBV effect on stock prices. Meanwhile, NPM has no effect on stock prices. From the Moderation Regression Analysis, it was found that EPS was able to moderate ROA and PBV. Meanwhile, EPS is not able to moderate NPM.